Constructing national identity and ethnic identity to children: A study case of Chinese Indonesian parents in Surabaya, Indonesia - Sally Azaria (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2022)
Parents play an important role in their children’s identity development, especially at the age of 8 to 13. Failure to form this identity will cause a negative impact on their children and others. This study examined Chinese Indonesian parents in constructing national identity and Chinese identity for their children. The approach used was a qualitative method using thematic analysis to analyze the data. This research used 20 participants from Chinese Indonesian parents, aged 30 to 45 years old, who have children aged 8 to 13, living in Surabaya, Indonesia. The results showed that all participants had a national identity; none of them had a transnational identity. However, they did not structurally construct this identity because they felt their children would get that from school. The construction of national identity and Chinese identity could go conjointly without damaging either identity. None of them opposed their children having Chinese identities. They came from two groups: those allowing the construction to occur naturally and those carrying them deliberately. This study concludes emphasized the importance of parents’ active involvement in the process of identity development so that their children could successfully balance themselves between having a national identity and ethnic identity.